Synthesis of an unusual quinazoline alkaloid: theoretical and experimental investigations of its structural, electronic, molecular and biological properties. Issue 15 (23rd February 2018) - Lone, Shabir H.; Jameel, Salman; Bhat, Muzzaffar A.; Lone, Rayees A.; Butcher, Ray J.; Bhat, Khursheed A.
Abstract : A comparative overview of theoretical and experimental studies concerning the electronic, structural and biological domains of the synthesized unusual quinazoline alkaloid is presented. Abstract : An unusual quinazoline alkaloid (1 ) was obtained when 2-aminobenzaldehyde was refluxed with pyrrolidine in ethanol for 12 h. The synthesized compound was characterized using spectral data analysis augmented with X-ray and literature precedent. Single crystal analysis depicted four conformations differing slightly in bond angles and bond lengths. Compound1 crystallizes in a triclinic crystal system with a P 1̄ space group having two molecules within the unit cell. The experimentally obtained parameters were compared to those obtained theoretically, which depicted a good agreement. Using the DFT/B3LYP/6-31G (d, p) level of theory, HOMO–LUMO energy gap, molecular electrostatic potential (MEP), vibrational (IR) and NMR analyses were carried out. The HOMO–LUMO energy gap allowed the calculation of chemical hardness, chemical inertness, electronegativity and the electrophilicity index of the molecule, which depicted its potential kinetic stability and reactivity. Prediction of activity spectra of the target compound revealed that compound1 possesses notable antineoplastic activity with P a = 0.884. The molecule was therefore evaluated against various cancerous cell lines in an in vitro SRB assay which depicted that compound1 possesses the highest growth inhibition activity against THP-1 cell lines with an IC50 of 7 μM.